Rational materials design for stable interfaces in all-solid-state potassium-ion batteries - Kim, Sooyeon; Jang, Myeongcho; Yu, Seungho (Royal Society of Chemistry, 2025)
All-solid-state potassium-ion batteries (ASSPIBs) are an emerging class of energy storage systems that offer a safe and cost-effective solution for large-scale applications. However, their development has been limited by interfacial chemical instability, and a comprehensive study has not yet systematically evaluated this critical aspect of ASSPIBs. In this work, inorganic potassium solid electrolytes (SEs) with high ionic conductivity were investigated, with emphasis on their electrochemical stability and chemical compatibility with cathode materials. Sulfide- and selenide-based SEs exhibited narrow stability windows and high decomposition energies at typical cathode potentials, whereas oxides showed moderate stability and chlorides provided the highest oxidative limits. Mutual reaction energy analysis revealed strong interfacial reactivity across most SE–cathode pairs, underscoring the need for protective strategies. To address this challenge, a high-throughput screening of more than 8000 potassium-containing compounds was performed, leading to the identification of twelve promising coating candidates. These materials significantly reduced interfacial reaction energies demonstrating their effectiveness in suppressing decomposition. This work establishes a rational design framework for stabilizing SE–cathode interfaces in ASSPIBs.